O ensino superior privado em Portugal: políticas e discursos - Ana Maria Seixas (Universidade do Minho, 2000)
In this paper the author describes the evolution of private higher education in Portugal from a peripheral to a mass system. After a brief description of its legal framework, some discourses about this system are analysed. The intention is to show which images are built and which arguments are set forward, which dimensions are consensual and where lie the biggest divergences as far as the role of the private higher education and its relation to the Portuguese State and society are concerned.